Systematic review of universal school-based resilience interventions targeting adolescent tobacco, alcohol or illicit drug use: review protocol. Issue 5 (26th May 2014) - Hodder, Rebecca Kate; Freund, Megan; Wolfenden, Luke; Bowman, Jenny; Gillham, Karen; Dray, Julia; Wiggers, John
Abstract : Introduction: Tobacco, alcohol and illicit drug use contribute significantly to global rates of morbidity and mortality. Despite evidence suggesting interventions designed to increase adolescent resilience may represent a means of reducing adolescent substance use, and schools providing a key opportunity to implement such interventions, existing systematic reviews assessing the effectiveness of school-based interventions targeting adolescent substance use have not examined this potential. Methods and analysis: The aim of the systematic review is to determine whether universal interventions focused on enhancing the resilience of adolescents are effective in reducing adolescent substance use. Eligible studies will: include participants 5–18 years of age; report tobacco use, alcohol consumption or illicit drug use as outcomes; and implement a school-based intervention designed to promote internal (eg, self-esteem) and external (eg, school connectedness) resilience factors. Eligible study designs include randomised controlled trials, cluster randomised controlled trials, staggered enrolment trials, stepped wedged trials, quasi-randomised trials, quasi-experimental trials, time series/interrupted time-series trials, preference trials, regression discontinuity trials and natural experiment studies with a parallel control group. A search strategy including criteria for participants, study design, outcome, setting and intervention will be implemented in various electronic databases and information sources. Two reviewers will independently screen studies to assess eligibility, as well as extract data from, and assess risk of bias of included studies. A third reviewer will resolve any discrepancies. Attempts will be made to quantify trial effects by meta-analysis. Binary outcomes will be pooled and effect size reported using ORs. For continuous data, effect size of trials will be reported using a mean difference where trial outcomes report the same outcome using a consistent measure, or standardised mean difference where trials report a comparable measure. Otherwise, trial outcomes will be described narratively. Dissemination: Review findings will be disseminated via peer-reviewed journals and conferences.